NCMP-10. IDH MUTATION STATUS AND THE DEVELOPMENT OF VENOUS THROMBOEMBOLISM IN ASTROCYTOMA PATIENTS. (9th November 2020) - Mandel, Jacob; Youssef, Michael; Yust-Katz, Shlomit; Patel, Akash; Jalali, Ali; Ludmir, Ethan; Wu, Jimin; de Groot, John
Abstract: OBJECTIVE: Examine whether the status of the isocitrate dehydrogenase ( IDH ) gene is a risk factor for the development of venous thromboembolism (VTE) in astrocytoma patients. BACKGROUND: The risk of venous thromboembolism (VTE) is high for patients with gliomas (10–30%). Unfortunately, biomarkers and predictive models for development of a VTE in brain cancer have not been validated. Prior research has suggested that IDH wildtype gliomas are at higher risk for development of VTE compared to IDH mutant tumors. DESIGN/METHODS: We conducted a retrospective chart review of glioma patients enrolled in the PROACTIVE (Prospective Assessment of Correlative Biomarker) study at MD Anderson Cancer Center (MDACC). We obtained demographics, date of tumor diagnosis, initial pathology, IDH s tatus (mutated or wildtype), extent of initial resection, KPS at time of initial resection, history of VTE, development of VTE, type of VTE (PE/DVT), KPS at time of VTE, treatment for VTE, bleeding complications, glioma treatments, date of last follow up and/or death. RESULTS: We identified 282 astrocytoma patients consisting of 49 IDH mutant and 233 IDH wildtype astrocytomas. Glioblastoma was the histopathologic diagnosis in 30 (61.2%) of the IDH mutated astrocytomas compared to 227(97.4%) of the IDH wild type astrocytomas. VTE was identified in 52 (18.4%) of patients. VTE was diagnosed in 7 (14.3%) of the IDH mutated astrocytomas compared to 45 (19.3%) of the IDH wild type astrocytomas (p = 0.4094). Median time to VTE from diagnosis was 2.71 months. Median time to VTE from diagnosis was 2.6 months for IDH mutated astrocytomas compared to 3.06 months for the IDH wild type astrocytomas (p =0.8663). CONCLUSIONS: IDH gene status did not appear as a significant risk factor for the development of venous thromboembolism (VTE) in our cohort of astrocytoma patients. Further research into potential biomarkers for VTE may be warranted.